Development and validation of student worker worksheets based on the RADEC learning model for Natural and Social Sciences (IPAS) subjects in elementary schools - Nurul Fatonah; Wahyu Sopandi; Hany Handayani; Yusup Maulana; Indra Gunawan; Indra Suhendra (xxxx-xxxx, 2023)
This research aims to develop and test the validity of student worksheet based on the RADEC Learning Model (Read, Answer, Discuss, Explain and Create) in Natural and Social Sciences (IPAS) subjects at elementary school level. The RADEC model is used as a basis for designing worksheets that support an active, participatory learning process and stimulate an in-depth understanding of science concepts. This research uses a development research approach. The development stage includes needs analysis, worksheet design, and validation by experts. It is hoped that the results of this research will contribute to improving worksheets as a learning aid that can improve students' understanding of science material in elementary schools. Apart from that, this research can also provide guidance to educators and students in implementing the RADEC Learning Model to improve the quality of learning in the classroom.